The Correlation Between Self-Confidence and Emotion Regulation with Learning Motivation Among Bullying Victims - Sasmita, Elsa Gita; Ekanesia, Pratidina (International Journal of Marketing & Human Resource Research, 2025)
Bullying, both verbal and nonverbal, can negatively impact students’ psychological well-being and academic engagement. This study examined the influence of self-confidence and emotion regulation on learning motivation among junior high school students who have experienced bullying. Using a quantitative correlational design, data were collected from 35 students selected through purposive sampling at a public school in Bandung Regency. Three validated psychological scales were used to assess self-confidence, emotion regulation, and learning motivation. Descriptive findings revealed that 97.2% of students had low self-confidence, and 54.29% had low learning motivation. Meanwhile, 57.14% of respondents demonstrated relatively high levels of emotion regulation. The regression analysis showed that self-confidence had a significant positive effect on learning motivation, while emotion regulation did not show a statistically significant influence when tested individually. However, when analyzed simultaneously, both variables contributed to 80.7% of the variance in learning motivation, indicating a strong joint influence. These findings suggest that psychological factors, particularly self-confidence, are crucial in shaping students’ academic motivation. Students with low confidence tend to avoid academic challenges and are less persistent, especially after experiencing bullying. Although emotion regulation alone was not a strong predictor, it supports emotional stability, which may indirectly affect learning behaviors. The study recommends school-based programs that focus on rebuilding students’ confidence and enhancing their ability to manage emotions. Providing a safe, supportive school environment is essential to prevent further psychological distress and to help students regain their motivation to learn.